(untitled) (Economic and Political Thought, 2016)
The scientific and technological revolution, as well as rapid acceleration in business processes on a global scale, affect labour and capital in an asymmetric manner. Capital is inherently more flexible than human beings, who, in addition to economic constraints, live in the network of social relations. The position of the working class is additionally weakened by process automation, replacing workers by increasingly intelligent robots. Our intention is to sketch a sequence of cause and effect of these processes: describe the basic aspects of the transformation of the labour market, their impact on trade unions and outline the future outlook for the trade union movement.